Phytoestrogens' beneficial effects on cardiovascular system (Medical Journal of Indonesia, 2002)
Several lines of evidence, including epidemiological, clinical trial and basic science, suggest the plausability of a causal, inverse relationship between phytoestrogens and cardiovascular disease. Phytoestrogens are naturally occurring plant compounds that have 2-phenylnaphthalene-type chemical structures similar to those of estrogens. they are simply divided into three main classes, isoflavones, lignans, and coumestans. The majority of phytoestrogens found in typical human diets are the isoflavones and lignans. This review provides an overview of the potential sources and bio-availability of the phytoestrogens particularly isoflavones, and discusses their beneficial effects on cardiovascular system, i.e. on atherosclerosis, hypercholestrolemia, arterial compliance, and blood pressure. (Med J Indones 2002; 11: 120-3)Keywords: atherosclerosis, hypercholestrolemia, arterial compliance, blood pressure